1, 25‐Dihydroxyvitamin D protects against age‐related osteoporosis by a novel VDR‐Ezh2‐p16 signal axis. Issue 2 (26th December 2019) - Yang, Renlei; Chen, Jie; Zhang, Jiao; Qin, Ran; Wang, Rong; Qiu, Yue; Mao, Zhiyuan; Goltzman, David; Miao, Dengshun
Abstract: To determine whether 1, 25‐dihydroxyvitamin D (1, 25(OH)2 D) can exert an anti‐osteoporosis role through anti‐aging mechanisms, we analyzed the bone phenotype of mice with 1, 25(OH)2 D deficiency due to deletion of the enzyme, 25‐hydroxyvitamin D 1α‐hydroxylase, while on a rescue diet. 1, 25(OH)2 D deficiency accelerated age‐related bone loss by activating the p16/p19 senescence signaling pathway, inhibiting osteoblastic bone formation, and stimulating osteoclastic bone resorption, osteocyte senescence, and senescence‐associated secretory phenotype (SASP). Supplementation of exogenous 1, 25(OH)2 D3 corrected the osteoporotic phenotype caused by 1, 25(OH)2 D deficiency or natural aging by inhibiting the p16/p19 pathway. The proliferation, osteogenic differentiation, and ectopic bone formation of bone marrow mesenchymal stem cells derived from mice with genetically induced deficiency of the vitamin D receptor (VDR) were significantly reduced by mechanisms including increased oxidative stress, DNA damage, and cellular senescence. We also demonstrated that p16 deletion largely rescued the osteoporotic phenotype caused by 1, 25(OH)2 D3 deficiency, whereas 1, 25(OH)2 D3 could up‐regulate the enzyme Ezh2 via VDR‐mediated transcription thereby enriching H3K27me3 and repressing p16/p19 transcription. Finally, we demonstrated that treatment with 1, 25(OH)2 D3 improved the osteogenic defects of human BM‐MSCs caused by repeated passages by stimulating their proliferation and inhibiting their senescence via the VDR‐Ezh2‐p16 axis. The results of this study therefore indicate that 1, 25(OH)2 D3 plays a role in preventing age‐related osteoporosis by up‐regulating Ezh2 via VDR‐mediated transcription, increasing H3K27me3 and repressing p16 transcription, thus promoting the proliferation and osteogenesis of BM‐MSCs and inhibiting their senescence, while also stimulating osteoblastic bone formation, and inhibiting osteocyte senescence, SASP, and osteoclastic bone resorption. Abstract : 1, 25(OH)2 D binds to the VDR, and the VDR‐RXR heterodimer then binds to the VDRE on Ezh2 up‐regulating Ezh2 and increasing H3K27met. This results in repression of p16/p19 transcription, thus promoting the proliferation of bone marrow MSCs and inhibiting their senescence and SASP production. Senescence and SASP production of osteocytes is also inhibited. As a consequence, osteoblastic bone formation is stimulated, and osteoclastic bone resorption is inhibited.